IMPLEMENTATION OF THE TOGAF FRAMEWORK ON A VIRTUAL TOUR OF WEB-BASED CILETUH GEOPARK TOURIST ATTRACTIONS - Ramdani Amarulloh; Muhammad Muslih; Nunik Destria Arianti (Jurnal Teknik Informatika (Jutif), 2022)
Ciletuh Geopark area is one of the marine tourism in Sukabumi regency. This tour has been recognized by UNESCO both nationally and internationally which now has changed its name to Ciletuh Geopark. However, in the management of information technology, there are still several problems, including the lack of information about the condition of the tourist attraction in Palabuhan Ratu Ciletuh Geopark, Sukabumi Regency. This study designed an information system based on a virtual tour website with the aim of being able to help tourists and the people to be able to find information online about Geopark Palabuhan Ratu Ciletuh tourist attraction, Sukabumi Regency with various existing tourist objects that can be accessed via the internet. This study uses the togaf framework where this framework has a systematic nature so that it is more flexible. Sources of data were taken by searching online from several sources related to the Ciletuh Geopark, Sukabumi Regency. The results obtained are in the form of a 3D virtual tour website where this website displays a 360 panorama along with information from each tourist attraction location as well as testing using blackbox and UAT (User Acceptance Test) every feature on the VIRGEO (Virtual Geopark) website has been fulfilled so that users can more easily access and find out the condition about Palabuhan Ratu Ciletuh Geopark tourist attraction, Sukabumi Regency easier.